Auditory distraction transmitted by a cochlear implant alters allocation of attentional resources - Finke, Mareike; Sandmann, Pascale; Kopp, Bruno; Lenarz, Thomas; Büchner, Andreas (Frontiers in Neuroscience, 2015)
Cochlear implants (CIs) are auditory prostheses which restore hearing via electrical stimulation of the auditory nerve. The successful adaptation of auditory cognition to the CI input depends to a substantial degree on individual factors. We pursued an electrophysiological approach towards an analysis of cortical responses that reflect perceptual processing stages and higher-level responses to CI input. Performance and event-related potentials on two cross-modal discrimination-following-distraction tasks from CI users and normal-hearing (NH) individuals were compared. The visual-auditory distraction task combined visual distraction with following auditory discrimination performance. Here, we observed similar cortical responses to visual distractors (Novelty-N2) and slowed, less accurate auditory discrimination performance in CI users when compared to NH individuals. Conversely, the auditory-visual distraction task was used to combine auditory distraction with visual discrimination performance. In this task we found attenuated cortical responses to auditory distractors (Novelty-P3), slowed visual discrimination performance, and attenuated cortical P3-responses to visual targets in CI users compared to NH individuals. These results suggest that CI users process auditory distractors differently than NH individuals and that the presence of auditory CI input has an adverse effect on the processing of visual targets and the visual discrimination ability in implanted individuals. We propose that this attenuation of the visual modality occurs through the allocation of neural resources to the CI input.